Four-Channel Buck-Type LED Driver with Automatic Current Sharing and Soft Switching - Wen-Zhuang Jiang; Kuo-Ing Hwu; Jenn-Jong Shieh (Applied Sciences, 2022)
A buck-type LED driver together with automatic current sharing and high step-down voltage conversion ratio but without complex control is proposed. The proposed LED driver can not only achieve zero voltage switching (ZVS) turn-on by adding only one resonant coupled inductor, which resonates with parasitic capacitors of active switches, but also can obtain lower voltage gain and better conversion efficiency. In this paper, the operating principles and design considerations of the proposed converter are discussed in detail. In addition, the number of LED strings can be extended to more than four channels. Finally, the theoretical analysis and performance of the proposed LED driver are verified by simulations and experiments using a field-programmable logic gate array (FPGA) named EP3C5E144C8N as a circuit control kernel.